Analysis of Breastfeeding Techniques with Breast Milk Production in the Postpartment Room of the Same Regional Hospital Nularan B Timor Leste Year 2020 - Flabiana Pareira Alfonso; Anggrawati Wulandari (Journal for Research in Public Health, 2021)
Breastfeeding is a valuable process and is a natural way of giving food to children. Many benefits we can get from giving. Babies get immune immunity from breast milk, therefore a good production of breast milk will make the financial process more successful. The purpose of this study was to analyze the relationship between testing techniques with ASI production. The method used in this research is correlational analytic with cross sectional research. The population is all mothers breastfeeding babies aged 0−2 days at the Same Hospital in East Timor B. The sampling technique uses accidental sampling. The independent variable is smoking technique and the dependent variable is the production of breast milk. The research instrument used questionnaires and observation sheets. Analysis of research results using the chi square test. The results showed, of the 23 respondents, 65.2% with correct breastfeeding techniques as many as 15 respondents, and 65.2% with a smooth production of Breast Milk as many as 15 respondents. The results also showed that the Exact Fisher's value obtained after the chi square test was 0.006 <0.05, which means there is a relationship between breastfeeding techniques and breast milk production at the Same Hospital area of ​​Timor Leste in 2020. The solution that needs to be done is to help with information through counseling by health workers about techniques that represent an important thing to avoid the lack of breast milk production. It is hoped that we as health workers will always provide counseling in the future through classes of pregnant women.